Analysis of Deadfreight Claim in the Process of Loading Coal on MV. Ocean Time - Sari, Latifa Ika; Imam, Muhammad Syarif Al (RSF Conference Series: Engineering and Technology, 2023)
Bahari Laju Anugerah Banjarmasin branch is a shipping company that handles and performs ship agency services in Banjarmmasin, South Kalimantan. The ships Handled are mostly ships that will transport coal to be exported to various countries in the world. In coal export activities, the transportation process from the jetty to the berth area is carried out using barges. During the loading and unloading/transshipment process, there are often obstacles that can cause dead freight which causes losses to the owner of the goods. This research was carried out in August 2021-February 2022. The purpose of this study is to determine the factors causing dead freight claims in the coal loading process on the MV. Ocean Time and the efforts made to reduce it. The research method in this study uses qualitative descriptive methods. Researchers use observation, interviews, and documentation (triangulation) in data collection. Researchers collect data as well as test the validity of the data by checking through several data sources such as conducting interviews with three different sources, namely Shipper on Board, Foreman on Board, and Foreman Jetty. The results of this research show that the cause of dead freight claims in the coal loading process on the MV Ocean Time is problems during the loading process, spillage of coal cargo during the loading process, and theft of coal cargo from the barge. To reduce it, several efforts were made by PT. Tanjung Alam Jaya as the owner of the cargo includes effective and efficient coordination and communication. In addition, by escorting the cargo carried by the barge so that the amount of cargo remains intact.